A contribution to the cranial morphology of the African burrowing lizard Feylinia polyepis (Bocage) - Du Toit, Francois Lassalle (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1971.